Correlation between Corporate Zakat, Capital Structures and Firm’s Performance: Case Study of Jakarta Islamic Index, Indonesia - Ummu Salma Al Azizah; Rito .; Muhammad Choirin (International Journal of Zakat, 2018)
The most important issue in corporate finance are how firms dealing with the structure of their capital and related to his performance. However, zakat payment and corporate tax will exist into the consideration of combination of debt and equity of the firms. In addition, there is an impact of capital structure on the performance of financial and non-financial firms operating in Indonesia for the period between 2013 an 2017. The data sampling taken from Jakarta Islamic Index companies, who has the report of zakat payment in their annual report.